A theoretical insight into the use of anti-reflective coatings for the upliftment of sensitivity of surface plasmon resonance sensors - Das, Chandreyee Manas (2021)
Surface Plasmon Resonance (SPR) based biosensors have been around in the scientific community for more than two decades and these have facilitated enormous improvement in the detection of complex biomolecules. Since, sensitivity of these sensors directly affects the ease of detection, our work here focuses on using dielectric nanosheets of Titania and Silica to enhance the sensitivity. The anti-reflective property of these dielectric materials promotes greater interaction between the incident light and the plasmonic metal, resulting in generation of more surface plasmons that promotes greater sensitivity. With 40 nm of gold, 3 layers of Titania (9 nm) and a layer of Silica (3 nm), our simulation results predict a sensitivity of 214 deg/RIU at 532 nm, which is a major improvement when compared to other sensor structures.